Gatekeeping Gender Equality: Curriculum Politics in Lithuanian Education - Drėgvaitė, Paulina (Acta Paedagogica Vilnensia, 2025)
This article investigates the challenges of implementing gender equality education in Lithuanian schools through the Life Skills Programme. By combining feminist pedagogy and discourse analysis, it reveals how gatekeeping by institutional actors and community resistance undermines national efforts at gender mainstreaming. The analysis demonstrates that gender equality education is a contested space shaped by ideological conflicts and power relations, rather than a straightforward curricular reform. The study highlights the need for ongoing engagement with both structural and human factors to foster meaningful change in post-socialist educational contexts.
Keywords: gender equality; education; Lithuania; Life Skills Programme